A Practical Guide to Bio-inspired Design - Hashemi Farzaneh, Helena; Lindemann, Udo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2019)
Bio-inspired design (also called biomimetics or biomimicry) is a promising approach for the development of innovative technical products - not only in mechanical engineering, but also in areas such as material science and even computer engineering. Innovations such as humanoid robots or multifunctional materials have shown the potential of bio-inspired design. However, in industrial companies, bio-inspired design remains an "exotic" approach which is rarely used in innovation practice. One reason for this is a lack of knowledge on how to implement bio-inspired design in practice. Therefore, this guide book was written to explain the application of bioinspired design methods and tools. The target groups are professional engineers and biologists, as well as students of both disciplines. The book presents a selection of methods for specific activities in bio-inspired design, namely: planning a bio-inspired design project, abstraction, search, analysis and comparison, and transfer of analogies. Factsheets give an overview of each method, its advantages and challenges, and its suitability for different bio-inspired design approaches and scenarios. To facilitate understanding, all methods are explained with the help of the same example. In addition, ten best practice examples show the practical applicability of bio-inspired design. The Authors Dr.-Ing. Helena Hashemi Farzaneh is a researcher at the Technical University of Munich. She studied mechanical engineering and received her PhD studying the collaboration between engineers and biologists. Her current research focuses on bio-inspired design and its integration into the innovation process. Professor Dr.-Ing. Udo Lindemann is a professor emeritus of the Technical University of Munich. He was formerly head of the Institute of Product Development (1995-2016). Udo Lindemann is active on several advisory boards, the National Academy of Science and Engineering, and is part of the Bavarian Industry Association Future council. For his outstanding achievements, he received the honorary title of "TUM Emeritus of Excellence".
Introduction -- Planning of a Bio-inspired Design Project -- Abstraction -- Search -- Analysis and Comparison -- Transfer of Analogies -- Fact sheets -- Refernces. Appendix. Index.
Keywords: Engineering design; Industrial engineering; Production engineering; Industrial design; Engineering Design; Industrial and Production Engineering; Industrial Design